Implementasi Program Magang MBKM di BKD Provinsi Kalimantan Tengah dalam Mempersiapkan Kompetensi Mahasiswa Memasuki Dunia Kerja - Abdul Karim; Nurul Hikmah (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
The policy for Independent Learning Independent Learning Campus (MBKM) internship activities is an example of a new idea in higher education that provides flexibility to students. In accordance with the mandate of Permendikbud Number 03 of 2020 concerning National Higher Education Standards, the Independent Learning Independent Campus (MBKM) was formed. Students of the IAIN Palangka Raya Islamic Education Management Study Program complete an internship assignment for one semester. The purpose of this program is to provide opportunities for students to apply the theories and knowledge that have been learned in lectures to the workplace situation. The method used is mentoring conducted by one Internship Assistance Lecturer to 4 participants for one semester. This internship activity is located at the Regional Staffing Agency of Central Kalimantan Province. The results of the office internship activities that have been carried out, student interns can do work practices and learn firsthand how the office administration system and staffing services at the BKD of Central Kalimantan province.